Manajemen Kurikulum Pondok Pesantren Darul Atqiya dalam Implementasi Program Wajib Belajar dan Kurikulum 2013 - Aom Muhtarom (CV Kalimasada Group, 2025)
This study aims to analyze curriculum management at Darul Atqiya Islamic Boarding School in Sindangkerta Maja in implementing the Nine-Year Compulsory Education program and the 2013 Curriculum. The research used a descriptive qualitative approach with observation, interviews, and documentation. The research subjects included school leaders, teachers, education staff, and students. The findings indicate that the curriculum was implemented through planning, implementation, and evaluation based on Islamic education principles and national education regulations. The school leader’s strategies focused on integrating the national curriculum with the traditional pesantren curriculum (kitab kuning), while teacher professionalism played a key role in the success of curriculum implementation. Despite challenges in lesson planning, authentic assessment, and limited facilities, the pesantren has shown positive achievements in improving education quality. The study concludes that curriculum management at Darul Atqiya Islamic Boarding School is relatively effective but requires stronger institutional support, teacher mentoring, and better alignment between the national curriculum and pesantren needs.